Near real‐time input to a propagation model for nowcasting of HF communications with aircraft on polar routes. Issue 7 (18th July 2016) - Warrington, E. M.; Stocker, A. J.; Siddle, D. R.; Hallam, J.; Al‐Behadili, H. A. H.; Zaalov, N. Y.; Honary, F.; Rogers, N. C.; Boteler, D. H.; Danskin, D. W.
Abstract: There is a need for improved techniques for nowcasting and forecasting (over several hours) HF propagation at northerly latitudes to support airlines operating over the increasingly popular trans‐polar routes. In this paper the assimilation of real‐time measurements into a propagation model developed by the authors is described, including ionosonde measurements and total electron content (TEC) measurements to define the main parameters of the ionosphere. The effects of D region absorption in the polar cap and auroral regions are integrated with the model through satellite measurements of the flux of energetic solar protons (>1 MeV) and the X‐ray flux in the 0.1–0.8 nm band, and ground‐based magnetometer measurements which form the Kp and Dst indices of geomagnetic activity. The model incorporates various features (e.g., convecting patches of enhanced plasma density) of the polar ionosphere that are, in particular, responsible for off‐great circle propagation and lead to propagation at times and frequencies not expected from on‐great circle propagation alone. The model development is supported by the collection of HF propagation measurements over several paths within the polar cap, crossing the auroral oval, and along the midlatitude trough. Key Points: Ray tracing method used to model the effects of the polar ionosphere on HF signals Background ionosphere based on IRI with parameters derived from TEC measurements Polar cap features, e.g., patches, included in the model